Persuasionsstrategien in der Gesundheitskommunikation.: Eine vergleichende Analyse am Beispiel von Impfungskampagnen in Deutschland, Italien und den Niederlanden - Magris, Marella; Ross, Dolores (Linguistik Online, 2019)
So far, linguistic and translational studies on medical communication have mostly foregrounded the referential function prevailing in texts of this domain. On the contrary, the relatively young discipline of health communication has been paying great attention to persuasive aspects, as shown by the fact that some definitions of the discipline itself and/or of its subject explicitly mention the influence on attitudes and behaviour as one of the goals. The present paper tries to bring these different perspectives closer to each other by adopting a content-based typology of persuasive strategies and applying it to a linguistic analysis in three languages, i. e. German, Italian and Dutch. The analysis has been carried out on a small corpus of vaccination brochures, as immunisation is currently one of the most debated topics of public health, and therefore an area where persuasion can play a far from secondary role. The comparison between the three languages will highlight some analogies, but also some differences which can be of relevance for translators and other language experts working in this field.